Major endothelial damage markers identified from hemadsorption filters derived from treated patients with septic shock – endoplasmic reticulum stress and bikunin may play a role - Kasper, Robin; Rodriguez-Alfonso, Armando; Ständker, Ludger; Wiese, Sebastian; Schneider, E. Marion (Frontiers in Immunology, 2024)
Introduction: In septic patients the damage of the endothelial barrier is decisive leading to circulatory septic shock with disseminated vascular coagulation, edema and multiorgan failure. Hemadsorption therapy leads to rapid resolution of clinical symptoms. We propose that the isolation of proteins adsorbed to hemadsorption devices contributes to the identification of mediators responsible for endothelial barrier dysfunction. Material & Methods: Plasma materials enriched to hemadsorption filters (CytoSorb®) after therapy of patients in septic shock were fractionated and functionally characterized for their effect on cell integrity, viability, proliferation and ROS formation by human endothelial cells. Fractions were further studied for their contents of oxidized nucleic acids as well as peptides and proteins by mass spectrometry. Results: Individual fractions exhibited a strong effect on endothelial cell viability, the endothelial layer morphology, and ROS formation. Fractions with high amounts of DNA and oxidized DNA correlated with ROS formation in the target endothelium. In addition, defined proteins such as defensins (HNP-1), SAA1, CXCL7, HNP-1 and the peptide bikunin were linked to the strongest additive effects in endothelial damage. Conclusion: Our results indicate that hemadsorption is efficient to transiently remove strong endothelial damage mediators from the blood of patients with septic shock, which explains a rapid clinical improvement of inflammation and endothelial function. The current work indicates that a combination of stressors leads to the most detrimental effects. Oxidized ssDNA, likely derived from mitochondria, SAA1, the chemokine CXCL7 and the human neutrophil peptide alpha-defensin 1 (HNP-1) were unique for their significant negative effect on endothelial cell viability. However, the strongest damage effect occurred, when, bikunin – cleaved off from alpha1-microglobulin was present in high relative amounts (>65%) of protein contents in the most active fraction. Thus, a relevant combination of stressors appears to be removed by hemadsorption therapy which results in fulminant and rapid, though only transient, clinical restitution.